The Effects of Melatonin On The Oxidative Stress , Protein Glycation , Microalbuminuria and Lipid Profile In Type II Diabetes Mellitus - Hasan M.H. Alâ€"Mhbashy; Saad A. Hussain; Nawfal A.M. Numan; Majeed A. Saed (College of Pharmacy University of Baghdad, 2017)
Previous studies indicated that supplementation with antioxidants has a protective effects against oxidative stressâ€"induced damage in type 2 diabetes. In this study we evaluated the antioxidant effects of melatonin on the oxidative stress parameters and microalbuminuria in type 2 DM patients. 30 patients with type 2 DM were treated with 3mg/day melatonin for 90 days. Erythrocytes and plasma MDA and glutathione, fasting plasma glucose, %HbAIC, microalbuminuria, total plasma protein and lipid profile were measured each 30 days and compared with those obtained from 20 healthy controls. A decrease in MDA levels associated with the elevation in GSH levels were observed, compared with the preâ€"treatment levels. Fasting plasma glucose, glycated hemoglobin and microalbuminuria were significantly decreased, associated with an improvement in the total cholesterol, HDLâ€"C and LDLâ€"C levels, with respect to the pretreatment values.In conclusion , treatment of type 2 DM patients with melatonin may have protective effects against the oxidative stressâ€"induced damage during the course of type 2 DM. Key words: Diabetes Mellitus, Oxidative Stress, Melatonin,Microalbuminuria.